The effects of exercise on antenatal depression: a systematic review and meta-analysis - Zhang, Zheng; Liu, Yun Jia; Sun, Lin; Zhao, Xiao-Dong (Frontiers in Psychiatry, 2024)
The aim of this study was to conduct a systematic evaluation of exercise interventions' effectiveness on antenatal depressive symptoms in pregnant women and to investigate the impact of different intervention factors on the relationship between exercise and antenatal depressive symptoms. METHODS: We conducted comprehensive searches in several databases, including PubMed, Embase, Web of Science, Cochrane Library, and others. The search period covered from database inception to May 2023. After thorough screening, a total of 7 papers with 524 subjects were included in the analysis.The meta-analysis revealed that the overall effect size of exercise intervention on antenatal depressive symptoms in pregnant women was SMD = -0.41, with a 95% confidence interval of [-0.78, -0.05], and P = 0.03, indicating a significant improvement in depressive symptoms due to exercise intervention during the antenatal period. However, some degree of heterogeneity was observed among the studies, with I² = 74%, P = 0.0007.The results indicate that exercise interventions significantly contribute to the improvement of antenatal depressive symptoms in pregnant women, as inferred from the combined findings of the studies. Notably, static exercise intervention showed better results than dynamic exercise intervention. Moreover, interventions conducted before 20 weeks' gestation had superior outcomes compared to those conducted after 20 weeks' gestation, and interventions lasting longer than the trimester duration exhibited more favorable effects than shorter interventions. However, to validate these findings and optimize exercise intervention protocols for